A new species of Astyanax (Characiformes: Characidae) from Costa Rica and Panama, with a key to the lower Central American species of the genus. Issue 6 (26th April 2018) - Angulo, A.; Santos, A. C.; López, M.; Langeani, F.; Mcmahan, C. D.
Abstract : Astyanax anai, a new species of characid fish, is described from the Sixaola River basin, eastern Costa Rica–western Panama, Central America. The new species can be distinguished from all other congeners by the following combination of characters: premaxillary teeth 4–5 at the inner series and 4–6 at the outer series; maxillary teeth tricuspid, 2–4; predorsal scale series irregular and incomplete, with an unscaled space behind tip of supraoccipital process and 12–14 scales; lateral line scales 34–39; humeral region with a conspicuous black and rounded to horizontally ovate spot and two diffuse brown and vertically elongate bars (the first through the rounded to horizontally ovate spot, the second 2–4 scales behind the first); body depth 36·6–42·3% of standard length ( L S ); midlateral stripe formed by a series of 10–14 anteriorly‐directed dermal herringbone, or chevron‐shaped, marks, most apparent in juveniles and in preserved specimens, extending above the lateral line from the black humeral spot or just behind it (from the second vertical bar) to the caudal peduncle; scale rows from lateral line to base of first dorsal‐fin ray 8–9; scale rows from lateral line to base of pelvic fin 7–8; pre‐anal distance 53·9–61·9% of L S ; total anal‐fin elements 29–33; caudal spot elongated, rhomboid or rectangular, with its anterior margin surpassing the middle of the caudal peduncle, usually reaching the anal‐fin insertion, posteriorly covering 4–7 principal caudal‐fin rays and not extending onto the ventral and dorsal margins of the caudal peduncle, covering 3–5 horizontal scale rows. In order to test the phylogenetic relationships of the new taxon in relation to the other North and Central American species of the genus, a new phylogenetic hypothesis based on a reanalysis of the morphological matrix by Schmitter‐Soto (2016) is proposed. A key to the lower Central American (southern Nicaragua to eastern Panama) species of Astyanax is also provided.